ANALISIS SISTEM KOMPENSASI CAFE ABC DENGAN METODE ADHERED DAN OVERLAPPING - Annisa Dayana Salsabilla; Atika Zahra; Farras Berlian Islami; Lili Nur Kusuma Dewi; Siti Nur Azizah Putri Wangi; Lindawati Kartika (Jurnal Pijar, 2023)
One function of human resource management that deals with all types of employee rewards in exchange for performing tasks is known as compensation. Cafe ABC is engaged in the culinary field which is located in the center of Bogor City. The purpose of this study is to analyze the compensation system for employees so that organizational productivity achieves goals effectively and efficiently. The research method used includes salary mapping with adhered and overlapping methods. The results obtained from this research are the adhered method is preferred over the overlapping method at Cafe ABC.